ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KETEPATWAKTUAN PELAPORAN KEUANGAN PADA PERUSAHAAN SUB SEKTOR PERTAMBANGAN LOGAM DAN MINERAL LAINNYA YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2013-2018 - Parwoko, Wiwit Hadi; Astuti, Dewi Saptantinah Puji; Sunarti, Sunarti (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2020)
This study aims to find empirical evidence about the factors that affect thetimeliness of financial reporting of other metal and mineral mining sub-sectorslisted on the Indonesia Stock Exchange. The factors tested in this study areprofitability, company age, company size, leverage, liquidity, KAP reputation andownership structure. The sample in this study used 8 metal and mineral miningsub sector companies listed on the Indonesia Stock Exchange in the period 2013-2018 taken using purposive sampling. These factors are then tested by logisticregression at a significance level of 5 percent. The results of the study identifiedthat company age and KAP's reputation had a significant effect on the timelinessof financial reporting, while profitability, company size, leverage, liquidity andownership structure did not affect the timeliness of financial reporting in othermetal and mineral mining sub-sectors listed on the Indonesia Stock Exchange.